The body as evidence of the soul in Plato’s Gorgias - Montenegro, Maria Aparecida de Paiva; Santiago, Pedro Henrique Araújo (Revista Archai, 2020)
We intend to point out that in the Gorgias, dialogue devoted to the critique of rhetoric, Socrates' frequent allusions to the body's complexion, and the recurrent use of corporeal metaphors to refer to what, by analogy, happens to the soul, function as a rhetoric tool in order to oppose Gorgias' own rhetoric. Thus, while drawing attention to the way Plato uses the weapons of the adversary precisely to attack him, we emphasize the indispensable role of the body as evidence of the soul in Platonic philosophy. Therefore, our intent is to reinforce the interpretive strand according to which Plato can be understood more as a thinker who departs from the pressing problems of his time in order to lead us into philosophical reflections ”“ in the present dialogue, the political consequences of a paideia oriented by sophistic rhetoric ”“, than as a philosopher solely committed to a transcendent metaphysics.